The role of the industrial engineer in al energy system development - Ortiz Ulloa Juvenal Alejandro; Facultad de Ciencias Qum̕icas, Universidad de Cuenca
En la actualidad se investigan ml͠tiples formas de proveer energa̕ a partir de recursos renovables y de una eficiente explotacin̤ de recursos convencionales. Se piensa que esta tarea concierne n͠icamente a ciertas ramas especializadas como la qum̕ica, la mecǹica, la electricidad o la hidrùlica. Sin embargo, la Ingeniera̕ Industrial representa un conjunto de destrezas que permiten agregar valor a investigaciones relacionadas a este tema. Un sistema energťico comprende varios aspectos interconectados entre los cuales estǹ: La materia prima o recurso primario a explotar, el proceso de conversin̤ de energa̕, el producto deseado y la demanda a satisfacer. Todos estos aspectos son variables que deberǹ ser estudiadas en conjunto.Un ingeniero industrial posee capacidades n͠icas como planificador y administrador que le permiten optimizar y gestionar adecuadamente los recursos utilizados en un proyecto de este tipo. En este estudio se presenta algunas de las aplicaciones del perfil del ingeniero industrial en el desarrollo de un sistema energťico.IntroductionThe current energy supply is oil dependent for most countries, particularly for industrializedeconomies like the United States, China or India [1]; for other countries, oil became the mosti mportant income generator [2]. This situation urges to develop new energy systems capable to overtake the oil industry in cost and efficiency. Nonetheless, this task entails challenges interms of source availability, process design and logistics. For that reason, an energy systemmust be planned by a multidisciplinary team in different stages such as: Conversion technologies, supply and demand management, financial and cost analysis. A modern Industrial Engineer, from an industry point of view, must be educated in emerging topics like: Project management, optimization methods, financial engineering and lean enterprise [3]. It means that not only the nowadays engineer, but the new Industrial Engineercan apply its knowledge to deal with most of the relevant aspects of an energy system development. According to [4] the Industrial Engineer can make a research career analyzingthe interaction between energy, environment and industry, increasing the efficiency of the processes and reducing emissions. The later statement implies that these engineers must have knowledge in terms of energy systems functioning, therefore, that knowledge could be used during the development of a new energy system